2018
DOI: 10.1177/0022185618801396
|View full text |Cite
|
Sign up to set email alerts
|

Intensification of teachers’ work under devolution: A ‘tsunami’ of paperwork

Abstract: Australian public school teachers work some of the longest weekly hours among Organisation for Economic Co-operation and Development countries, particularly in the state of New South Wales where average hours are officially in, or near, the statistical category of ‘very long working hours’. These reports of a high workload have occurred alongside recent policy moves that seek to devolve responsibility for schooling, augmenting teacher and school-level accountability. This article explores changes in work deman… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
22
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
5

Relationship

2
8

Authors

Journals

citations
Cited by 63 publications
(24 citation statements)
references
References 55 publications
1
22
0
1
Order By: Relevance
“…A recent study of Australian teachers found that data collection and reporting were one of the main systemic sources of stress (Carroll, Flynn, et al, 2021). Another consideration is that the intensification of teaching may differentially affect primary and secondary school teachers (see Fitzgerald et al, 2019). Primary teachers are more generalist, have more face-to-face time with their students (McKenzie et al, 2014), and more contact with their students' parents than secondary school teachers (Saltmarsh et al, 2015) all of which may potentially contribute to their levels of stress and burnout; more research is needed however.…”
Section: Stress and Burnout Profiles Across Teacher Characteristicsmentioning
confidence: 99%
“…A recent study of Australian teachers found that data collection and reporting were one of the main systemic sources of stress (Carroll, Flynn, et al, 2021). Another consideration is that the intensification of teaching may differentially affect primary and secondary school teachers (see Fitzgerald et al, 2019). Primary teachers are more generalist, have more face-to-face time with their students (McKenzie et al, 2014), and more contact with their students' parents than secondary school teachers (Saltmarsh et al, 2015) all of which may potentially contribute to their levels of stress and burnout; more research is needed however.…”
Section: Stress and Burnout Profiles Across Teacher Characteristicsmentioning
confidence: 99%
“…Research from a variety of national contexts including Canada (Wang et al, 2018), Australia (Niesche, 2018) and the US (Reid, 2020) has focused on the increased intensification of principals' work as a consequence of marketised education policy manoeuvres, variously related to accountability, performativity and the creation of competitive systems. Recent work from Australia has suggested that work intensification manifests as both an increase in workload causing a 'constant conflict' in how to allocate time, with a kind of 'triage effect' coming into play (McGrath-Champ et al, 2019), and as a shift in the kind of work required, away from core educational work to administrative 'paperwork' tasks (Fitzgerald et al, 2019).…”
Section: Work Intensificationmentioning
confidence: 99%
“…Meanwhile governments consistently attribute broader social and economic problems to (public) education systems that deliver supposedly poor academic outcomes (Helsby, 1999). Moreover, eroding system-level support has contributed to intense workload pressures for teachers in an industrial relations framework that has restricted union capacity to improve wages and conditions (Fitzgerald et al, 2019;Gavin, 2019). The structural, institutional and regulatory challenges facing public sector unions, including teachers' unions, in a neoliberal environment have therefore required a re-imagining of the power resources drawn upon and strategic capabilities enacted to dually advance union goals of improving the industrial/professional conditions of teachers and defending the essential (public) services delivered in the community (Bascia and Stevenson, 2017).…”
mentioning
confidence: 99%